An Anticancer Tannin and Other Phenolics from Limonium axaillare (Fam. Plumbaginaceae) - M. Ahmed, Khadiga; E. Kandil, Fayez; J. Mabry, Tom (Asian Journal of Chemistry, 2010)
Flavonoids, phenolics, coumarins and condensed tannins were isolated and identified from the leaves of Limonium axaillare. This is the first report of an ellagitannin, geraniin, from this genus. The anticancer activity of geraniin was found to be slightly higher than that of the crude extract.